2015
DOI: 10.1177/0275074015616868
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Resilience: Evidence From the Management of Senior Low-Income Housing

Abstract: Although public and private management approaches have been frequently analyzed for their outcomes along the lines of efficiency and equity, their relationship to fostering community resilience has been understudied. Public housing has undergone a market-based transition, devolving management and operations of its sites or tenants to private management companies. This multi-site case study evaluates different management contexts to understand how management processes encourage or discourage community resilienc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Housing staff usually consisted of a building manager (e.g., Bernstein, 1982; Heumann, 1988; Robbins et al, 2000) and maintenance staff (Heumann, 1988). Although these staff were typically hired for their skills in managing the physical and fiscal property, they frequently engaged in tenant-support activities (Heumann, 1988), despite no formal training to fulfill this role (Lucio & McFadden, 2017; Suggs et al, 1986). Most housing managers reported that they had limited knowledge of which older tenants were experiencing difficulties managing their units and/or health (Heumann, 1988) and expressed a need for more training in identifying at-risk tenants and connecting them to services (Sheehan & Wisensale, 1991).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Housing staff usually consisted of a building manager (e.g., Bernstein, 1982; Heumann, 1988; Robbins et al, 2000) and maintenance staff (Heumann, 1988). Although these staff were typically hired for their skills in managing the physical and fiscal property, they frequently engaged in tenant-support activities (Heumann, 1988), despite no formal training to fulfill this role (Lucio & McFadden, 2017; Suggs et al, 1986). Most housing managers reported that they had limited knowledge of which older tenants were experiencing difficulties managing their units and/or health (Heumann, 1988) and expressed a need for more training in identifying at-risk tenants and connecting them to services (Sheehan & Wisensale, 1991).…”
Section: Resultsmentioning
confidence: 99%
“…From the tenant perspective, tenant support staff were key sources of companionship and provided a sense of security (Schulman, 1996; Sheehan, 1999); they also helped foster more positive relationships between tenants (Blandford et al, 1989) and created a community-like environment where older tenants were empowered to have a stronger voice in the management of the building (Lucio & McFadden, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has illustrated how management can implement institutional support in order to leverage the actions of elderly residents living in public housing (Lucio & McFadden 2015). In this same vein, results of the current study can be used to guide policy or program suggestions that leverage both the actions and the community structure of public housing developments.…”
mentioning
confidence: 87%